Knowledge and Anxiety in Community During the COVID-19 Pandemic - Zidni Nuris Yuhbaba; M. Elyas Arif Budiman; Irwina Angelia Silvanasari; Wahyi Sholehah Erdah Suswati (Babali Health, 2022)
Introduction: The continuous increase in COVID-19 data can cause public anxiety increase. Good knowledge of the COVID-19 pandemic is important to prevent anxiety because with knowledge the individual will have the ability to determine and make decisions on how he can deal with it so that it can minimize the risk of the emergence of anxiety. The purpose of this study was to describe the knowledge and anxiety of the community during the COVID-19 pandemic. Methods: This study used a cross-sectional method, carried out by distributing a google form link to respondents. The number of samples in this study were 115 respondents taken using purposive sampling technique then the data was analyzed using the SPSS application and only displayed the distribution of frequency and percentage. Results: The results showed that the level of knowledge of respondents about the COVID-19 pandemic was in the good knowledge category of 80.8% and the level of anxiety was in the category of not experiencing anxiety as much as 86%. Conclusion: A person's level of knowledge in dealing with the COVID-19 pandemic can be a factor that affects the emergence of anxiety disorders.